2011
DOI: 10.1186/1744-8069-7-69
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Relief from Intermittent Cold Stress-Induced Fibromyalgia-Like Abnormal Pain by Repeated Intrathecal Administration of Antidepressants

Abstract: BackgroundFibromyalgia (FM) is characterized by chronic widespread pain, which is often refractory to conventional painkillers. Numerous clinical studies have demonstrated that antidepressants are effective in treating FM pain. We previously established a mouse model of FM-like pain, induced by intermittent cold stress (ICS).ResultsIn this study, we find that ICS exposure causes a transient increase in plasma corticosterone concentration, but not in anxiety or depression-like behaviors. A single intrathecal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…In the present study, we found that repeated administration of tramadol and amitriptyline prevented and alleviated neuropathic pain via the a 2 -AR. Consistent with our findings, several studies reported that repeated administration of TCAs, as well as SNRIs, alleviated peripheral nerve injury-induced neuropathic pain (45,46), intermittent cold stress-induced fibromyalgia abnormal pain (47), and oxaliplatin-induced painful neuropathy (48). The preventive effects of tramadol and amitriptyline were diminished by pretreatment with yohimbine, suggesting that the effects involved stimulation of the a 2 -AR.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we found that repeated administration of tramadol and amitriptyline prevented and alleviated neuropathic pain via the a 2 -AR. Consistent with our findings, several studies reported that repeated administration of TCAs, as well as SNRIs, alleviated peripheral nerve injury-induced neuropathic pain (45,46), intermittent cold stress-induced fibromyalgia abnormal pain (47), and oxaliplatin-induced painful neuropathy (48). The preventive effects of tramadol and amitriptyline were diminished by pretreatment with yohimbine, suggesting that the effects involved stimulation of the a 2 -AR.…”
Section: Discussionsupporting
confidence: 78%
“…This model has shown characteristics of a generalized chronic pain phenotype and shares female-predominant sex differences and pharmacotherapeutic features with fibromyalgia patients. Specifically, ICS-induced pain is sensitive to gabapentin and antidepressants (Nishiyori and Ueda, 2008;Nishiyori et al, 2011), but not to morphine (Nishiyori et al, 2010), which is consistent with the clinical evidence of fibromyalgia patients (Clauw, 2014).…”
Section: Introductionsupporting
confidence: 58%
“…The most important finding was observed in the complete amelioration of chronic pain, even after the cessation of donepezil treatments, implying that pain memory in fibromyalgia might disappear after repeated treatments with donepezil. Likewise, a complete amelioration of chronic pain in the ICS model has also been observed when antidepressants, such as milnacipran, amitriptyline, mianserin, and paroxetine, are repeatedly administered by intrathecal injection (Nishiyori et al, 2011). Thus, chronic pain in this model may be maintained by vicious cycles, which include the attenuation of a spinally descending, pain inhibitory system and enhancement Cholinomimetics for the Treatment of Fibromyalgia within pain matrices in the brain.…”
Section: Discussionmentioning
confidence: 95%
“…Induction of stress in animals (swim stress, cold stress) can itself produce muscle and cutanoeus hyperalgesia that lasts for weeks after the stressor (Quintero et al, 2000, Quintero et al, 2003, Suarez-Roca et al, 2006, Nasu et al, 2010, Nishiyori et al, 2011). On the other hand, milder stressors (fatigue, sound stress) that do not produce hyperalgesia on their own, can enhance and prolong the hyperalgesic response to a subthreshold or mild noxious stimulus (Yokoyama et al, 2007b, Khasar et al, 2009, Sluka and Rasmussen, 2010, Sluka et al, 2012, Gregory et al, 2013).…”
Section: Stress and Psychological Factors Are Involved In The Developmentioning
confidence: 99%
“…The stressor can lead to increases in plasma cortisone levels (Nishiyori et al, 2011) or long-lasting increased activity of catecholamine synthesizing enzymes in the adrenal medulla (Khasar et al, 2008, Khasar et al, 2009) that results in increased plasma levels of epinephrine for at least 28 days after the last exposure to sound stress (Khasar et al, 2009) suggesting that a long-lasting stress-induced alteration in the animal that persists well beyond exposure to the starting stress factor. Decreasing expression of interleukin-6 receptor (IL-6) on primary afferent neurons prevents the enhanced response to noxious stimuli (Dina et al, 2011a) suggesting alterations in cytokines and the HPA axis may underlie stress-induced enhancement of hyperalgesia.…”
Section: Stress and Psychological Factors Are Involved In The Developmentioning
confidence: 99%